دراسة مبدئية لتأثير المضاد لنبات بلحة جحا على إنبات بذور وتطور بادرات نبات الفجل - الزربي عبد الحميد (Scientific Journal of University of Benghazi, 2020)
Aim of the study was conducted investigate the effect of Allelopathy of aqueous extracts of leaves, flower and fruits of Ecbalium elaterium (L.) A. Rich at concentrations of 0.5%, 5% and 50% on seed germination and seedling development of Radish (Raphanus sativus L.). The results showed a difference in the Allelopathic effects on seed germination and development of seedling, indicating that extracts of leaves, flowers and fruits have an effect on reducing the percentage of germination and growth of the radical, especially at the concentration of 50% where germination was very low and sometimes completely inhabited. At 5%, concentration the effect was moderate while at 0.5% the effect was positive. The results also showed that the leaves extract had a higher effect compared to the effect of flowers and fruits extracts.